2019
DOI: 10.1017/s003118201900129x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in helminth infections: factors influencing aggregation in a simple host–parasite system

Abstract: The almost universally-occurring aggregated distributions of helminth burdens in host populations have major significance for parasite population ecology and evolutionary biology, but the mechanisms generating heterogeneity remain poorly understood. For the direct life cycle monogenean Discocotyle sagittata infecting rainbow trout, Oncorhynchus mykiss, variables potentially influencing aggregation can be analysed individually. This study was based at a fish farm where every host individual becomes infected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…fish older than one), and they attributed this pattern to an ontogenetic decline of susceptibility in older fish. Another study using a fish-monogenean system also found that adult individuals were more resistant than subadult (Konijnendijk et al 2013), demonstrating the importance of fish immunity in controlling monogenean infections (Buchmann and Bresciani 2006;Tinsley et al 2020). Thus, our results indicate a trade-off between the host resistance and parasite preference, resulting in high parasite burdens on subadult hosts.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…fish older than one), and they attributed this pattern to an ontogenetic decline of susceptibility in older fish. Another study using a fish-monogenean system also found that adult individuals were more resistant than subadult (Konijnendijk et al 2013), demonstrating the importance of fish immunity in controlling monogenean infections (Buchmann and Bresciani 2006;Tinsley et al 2020). Thus, our results indicate a trade-off between the host resistance and parasite preference, resulting in high parasite burdens on subadult hosts.…”
Section: Discussionsupporting
confidence: 71%
“…Although some fish parasite studies have shown that larger hosts are able to accommodate more parasite than small ones (Cantatore and Timi, 2015;Braicovich et al 2016), a decline of susceptibility in older fish also have been suggested to affect the fish infection outcomes (Tinsley et al 2020;Bailey et al 2021). In a recent experiment, Bailey et al (2021) found that the disease severity was greater in young than juvenile (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of local or intrinsic factors affect helminth aggregations in amphibians, such as spatial heterogeneity, host body size, parasite dimensions and virulence, and parasite and intermediatehost productivities (Campião et al, 2015;Johnson & Wilber, 2017;Toledo et al, 2017;Mihaljevic et al, 2018). In addition, fish studies suggest a high importance of individual host susceptibility (Tinsley et al, 2020) and show more complicated mechanisms determining helminth infection rates, such as ontogenic dietary shifts that change parasite intake pathways (Saad-Fares & Combes, 1992), or the presence of certain parasite infection levels that are optimal for the host body condition (Maceda-Veiga et al, 2016). Common invasion pathways or biological interactions (such as mutual facilitation or competition) may cause parasite species associations in hosts (Dallas et al, 2019) that, so far, have been noted in very few amphibian helminth community studies (Hamann et al, 2006a(Hamann et al, , 2010(Hamann et al, , 2013a(Hamann et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A hurdle model is a two‐part model that fits two linear models: the first a logistic linear model that estimates infection prevalence. The second part is a truncated negative binomial model that estimates infection intensity, as many parasitic infections show a negative binomial distribution (Pennycuick, 1971; Tinsley et al., 2020). The hurdle model was initially fit using all main effects (i.e.…”
Section: Methodsmentioning
confidence: 99%